2005
DOI: 10.2466/pms.100.1.61-68
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer Feedback to Promote Physical Activity in Adults with Type 2 Diabetes: A Pilot Study

Abstract: This study examined whether giving activity feedback to obese, sedentary adults with Type 2 diabetes would improve their adherence to a home-based walking program. 49 subjects were recruited. Ten failed a treadmill cardiovascular test. Another 9 dropped out before the intervention, and 4 dropped out during the intervention. The remaining 26 adults (14 women, 12 men; age M = 48.1 yr., SD = 7.1) received behavioral counseling monthly for 3 mo. regarding exercise. All subjects wore a triaxial accelerometer during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 15 publications
0
64
0
Order By: Relevance
“…walking, jogging, running), but less accurate for activities such as weight-lifting, swimming and cycling [25]. Since walking is the preferred type of physical activity in adults with type 2 diabetes [12] and previous research has supported the use of activity monitors to measure physical activity in individuals with diabetes [7,[26][27][28], we chose to objectively measure physical activity with ActiGraph uniaxial accelerometers (Manufacturing Technologies Incorporated, Fort Walton Beach, FL). The monitor was secured by a strap at the participant's right waist and programmed to collect activity counts at 1-min intervals over 7 days.…”
Section: 22mentioning
confidence: 99%
“…walking, jogging, running), but less accurate for activities such as weight-lifting, swimming and cycling [25]. Since walking is the preferred type of physical activity in adults with type 2 diabetes [12] and previous research has supported the use of activity monitors to measure physical activity in individuals with diabetes [7,[26][27][28], we chose to objectively measure physical activity with ActiGraph uniaxial accelerometers (Manufacturing Technologies Incorporated, Fort Walton Beach, FL). The monitor was secured by a strap at the participant's right waist and programmed to collect activity counts at 1-min intervals over 7 days.…”
Section: 22mentioning
confidence: 99%
“…37,38 None of the selected studies on pedometerbased interventions assessed issues of feasibility or usability. One trial using an accelerometer-based exercise intervention was reviewed 39 but did not fit the inclusion criteria.…”
Section: Self-monitoring Of Blood Glucose Devicesmentioning
confidence: 99%
“…Thirteen studies were identified, and of these, 4 met our inclusion criteria (Table 3). Studies were excluded because they did not report weight loss outcomes (nϭ3), [82][83][84] did not use a randomized controlled design (nϭ4), [85][86][87][88] or the phones used were standard landline phones (nϭ2). 49,89 All 4 studies enrolled primarily white women and were conducted in the community.…”
Section: Handheld and Other Devices For Use In Behavioral Weight Lossmentioning
confidence: 99%